Rippled Electron‐Scale Structure of a Dipolarization Front. Issue 22 (23rd November 2018) - Pan, Dong‐Xiao; Khotyaintsev, Yuri V.; Graham, Daniel B.; Vaivads, Andris; Zhou, Xu‐Zhi; André, Mats; Lindqvist, Per‐Arne; Ergun, Robert E.; Le Contel, Olivier; Russell, Christopher T.; Torbert, Roy B.; Giles, Barbara; et al.
Abstract: We use the Magnetospheric Multiscale mission to investigate electron‐scale structures at a dipolarization front. The four spacecraft are separated by electron scales and observe large differences in plasma and field parameters within the dipolarization front, indicating strong deviation from typically assumed plane or slightly curved front surface. We attribute this to ripples generated by the lower hybrid drift instability (LHDI) with wave number of k ρ e ≃0.4 and maximum wave potential of ∼1 kV ∼ k B T e . Power law‐like spectra of E ⊥ with slope of −3 indicates the turbulent cascade of LHDI. LHDI is observed together with bursty high‐frequency parallel electric fields, suggesting coupling of LHDI to higher‐frequency electrostatic waves. Plain Language Summary: Dipolarization fronts (DFs) are narrow boundaries with sharp enhancement of magnetic field, located at the leading part of fast plasma jets observed in Earth's magnetotail. DFs are typically assumed to be smooth boundaries at scales comparable to the ion gyroradius and below. In this study, we use the four Magnetospheric Multiscale spacecraft separated by several electron gyroradii to investigate fine structure of a DF. Surprisingly, we observe significant differences in the fields and plasma measurements between the spacecraft despite their small separation. We attribute these signatures to electron‐scale disturbances propagating along the DF surface, and thus the DF surface is not smooth as expected but rather rippled. The ripples develop as a result of a plasma instability driven by the strong inhomogeneities present at the DF. The fact that the ripples have such small scales means that they can effectively interact with plasma electrons. Key Points: Large differences in plasma and field parameters at electron spatial scales are observed within a dipolarization front The differences are consistent with ripples generated by lower hybrid drift instability (LHDI) Power law‐like spectra forE andB indicate a turbulent cascade of LHDI